Exploring relationships between health professionals through the implementation of a reablement program for people with dementia: A mixed methods study. Issue 3 (20th December 2020) - Culph, Jennifer; Clemson, Lindy; Scanlan, Justin; Craven, Luke; Jeon, Yun-Hee; Laver, Kate
Abstract: Aims: Implementation of novel interventions occurs within broad organisational contexts, which contain many relationships and moving parts. Efforts need to be made to understand these relationships as they are an important predictor of successful implementation. This study examines the relationships between health professionals involved in the implementation of an evidence-based community program for people with dementia and their carers in Australia, The Care of People with dementia in their Environments program. Methods: This study utilised mixed methods including in-depth interviews and organisational diagrams. Qualitative data from 28 interviews were collected from occupational therapists, nurses and their managers. Recruitment ensured a variety of different organisational contexts were represented. Thematic analysis was used to capture key emergent themes. Findings: The strongest relationships were usually between the occupational therapist and their manager. Strong trusting relationships with managers were instrumental in advocating for the need for reablement programs and the occupational therapy professional role in dementia care. Large teams of occupational therapists were seen to be beneficial in supporting each other in case complexities. Relationships between occupational therapists and nurses were often missing or perceived as weak relationships. A conducive physical environment contributed to stronger more collaborative relationships, where individuals were visible and therefore felt to be more approachable. Conclusion: Our study highlights the additional preparation work that is required of organisations to consider relationships in their strategies for implementation.